Given that x 1 = 2 − x . x = 0
Evaluate the expression x 2 2 0 1 4 + x 2 2 0 1 4 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This the greatest solution my eyes have ever had the privilege to witness.
x 1 = 2 − x x + x 1 = 2 x x 2 + 1 = 2 x 2 + 1 = 2 x x 2 − 2 x + 1 = 0 ( x − 1 ) 2 = 0 x − 1 = 0 x = 1 ⟹ x 2 0 1 4 + x 2 0 1 4 1 = 1 2 0 1 4 + 1 2 0 1 4 1 x = 2 .
Look again at the problem!
Isn't it a bit obvious that x = 1 ? I don't know about you guys, I just saw that immediately. So when you evaluate the second bit, you get 1 + 1 = 2 .
It is obvious, but I wrote the equation like that on purpose, although it was useless actually.
Same with me Finn
Problem Loading...
Note Loading...
Set Loading...
Rewriting the equation, x 2 − 2 x + 1 = 0
( x − 1 ) 2 = 0 ⟹ x = 1
Hence, x 2 2 0 1 4 + x 2 2 0 1 4 1 = 2